The Role of Income on the Relationship Between the Brazilian Cash Transfer Program (Programa Bolsa Família) and Intimate Partner Violence: Evidence From a Multigroup Path Analysis - Leite, Tatiana Henriques (Journal of interpersonal violence, 2022)
Several initiatives are being proposed to reduce the incidence of intimate partner violence (IPV) worldwide. Actions aimed at women?s economic empowerment through income transfer programs are one of those. Still, the literature on their impact is scarce and controversial. This study attempts to shed some light on this matter assessing whether the Brazilian Conditional Cash Transfer Program (Programa Bolsa Família [PBF]) is a protective factor for psychological and physical IPV against women in families of different levels of income. This is a cross-sectional, household-based study conducted in the city of Duque de Caxias, Rio de Janeiro, Brazil. The sample comprised 807 women reporting some intimate relationship in the 12 months before the interview. Information on IPV and participation on PBF were collected through face-to-face interviews using the Revised Conflict Tactics Scales (CTS2) and a direct question, respectively. A multigroup path analysis was applied to study the relations between PBF and psychological and physical IPV, considering confounding factors, some mediators, and moderation by income. The prevalence of both psychological and physical IPV are high, be it in the poverty and the extreme poverty income strata (psychological IPV: 66.2% and 72.7%, respectively; physical IPV: 26.2% and 40.6%, respectively). Results also showed a positive and direct association between PBF and psychological violence, yet only among families above the poverty line (? = .287, p = .001). The same could be found regarding physical violence, but the effect of PBF was indirect, mediated by psychological violence (? = .220, p = .003). Findings suggest that actions aimed at preventing IPV should go hand in hand with the PBF and, perhaps, other income transfer programs. This is even more relevant in relation to the less extreme poverty group where cash transfer may further raise conflicts and violence.